2022
DOI: 10.3389/fped.2022.975826
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for admission to the pediatric critical care unit among children hospitalized with COVID-19 in France

Abstract: BackgroundCOVID-19 infection is less severe among children than among adults; however, some patients require hospitalization and even critical care. Using data from the French national medico-administrative database, we estimated the risk factors for critical care unit (CCU) admissions among pediatric COVID-19 hospitalizations, the number and characteristics of the cases during the successive waves from January 2020 to August 2021 and described death cases.MethodsWe included all children (age < 18) hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
0
3
1
Order By: Relevance
“…With a cohort of almost two hundred omicron patients compared with twenty-eight children with the original strain, the authors’ main findings are that younger children are more afflicted in the omicron cohort and that there is a seven-fold increase in PICU admissions. This finding contrasts to other studies that have compared the original to D614G to delta to omicron variant outcomes and subsequently shown that the PICU admission rate gradually decreased over these waves (from 31.0% to 17.8%) (13, 14). However, the authors in the present study failed to identify “any” association between epoch period and baseline comorbidity profile.…”
contrasting
confidence: 99%
“…With a cohort of almost two hundred omicron patients compared with twenty-eight children with the original strain, the authors’ main findings are that younger children are more afflicted in the omicron cohort and that there is a seven-fold increase in PICU admissions. This finding contrasts to other studies that have compared the original to D614G to delta to omicron variant outcomes and subsequently shown that the PICU admission rate gradually decreased over these waves (from 31.0% to 17.8%) (13, 14). However, the authors in the present study failed to identify “any” association between epoch period and baseline comorbidity profile.…”
contrasting
confidence: 99%
“… 20 Among hospitalized adolescents, children with underlying conditions, such as asthma, obesity, or sickle cell disease are overrepresented. 3 , 12 , 21 , 22 , 23 , 24 Rare cases of pulmonary embolism associated with COVID‐19 have also been reported in pediatric patients. 25 , 26 …”
Section: Clinical Symptoms Of Covid‐19 and Risk Factors For Severity ...mentioning
confidence: 99%
“…A systematic review of COVID‐19 in 63 infants under 3 months of age reported moderate severity and nonspecific clinical signs; however, one‐fifth of children required ICU care 20 . Among hospitalized adolescents, children with underlying conditions, such as asthma, obesity, or sickle cell disease are overrepresented 3,12,21–24 . Rare cases of pulmonary embolism associated with COVID‐19 have also been reported in pediatric patients 25,26 …”
Section: Clinical Symptoms Of Covid‐19 and Risk Factors For Severity ...mentioning
confidence: 99%
See 1 more Smart Citation